Risk Factors for Noninvasive Ventilation Failure in Children Post-Hematopoietic Cell Transplant - Rowan, Courtney M.; Fitzgerald, Julie C.; Agulnik, Asya; Zinter, Matt S.; Sharron, Matthew P.; Slaven, James E.; Kreml, Erin M.; Bajwa, Rajinder P.S.; Mahadeo, Kris M.; Moffet, Jerelyn; Tarquinio, Keiko M.; Steiner, Marie E. (Frontiers in Oncology, 2021)
Rationale Little is known on the use of noninvasive ventilation (NIPPV) in pediatric hematopoietic cell transplant (HCT) patients. Objective We sought to describe the landscape of NIPPV use and to identify risk factors for failure to inform future investigation or quality improvement. Methods This is a multicenter, retrospective observational cohort of 153 consecutive children post-HCT requiring NIPPV from 2010-2016. Results 97 (63%) failed NIPPV. Factors associated with failure on univariate analysis included: longer oxygen use prior to NIPPV (p=0.04), vasoactive agent use (p<0.001), and higher respiratory rate at multiple hours of NIPPV use (1hr p=0.02, 2hr p=0.04, 4hr p=0.008, 8hr p=0.002). Using respiratory rate at 4 hours a multivariable model was constructed. This model demonstrated high ability to discriminate NIPPV failure (AUC=0.794) with the following results: respiratory rate >40 at 4 hours [aOR=6.3 9(95% CI: 2.4, 16.4), p<0.001] and vasoactive use [aOR=4.9 (95% CI: 1.9, 13.1), p=0.001]. Of note, 11 patients had a cardiac arrest during intubation (11%) and 3 others arrested prior to intubation. These 14 patients were closer to HCT [14 days (IQR:4, 73) vs 54 (IQR:21,117), p<0.01] and there was a trend toward beginning NIPPV outside of the PICU and arrest during/prior to intubation (p=0.056). Conclusions In this cohort respiratory rate at 4 hours and vasoactive use are independent risk factors of NIPPV failure. An objective model to predict which children may benefit from a trial of NIPPV, may also inform the timing of both NIPPV initiation and uncomplicated intubation.